1987
DOI: 10.1038/clpt.1987.84
|View full text |Cite
|
Sign up to set email alerts
|

Sustained reductions in oxipurinol renal clearance during a restricted diet

Abstract: The renal clearance of oxipurinol, the major metabolite of allopurinol, was studied in six healthy subjects during normal and restricted (low protein and low calorie) diets. A 600 mg oral dose of allopurinol was administered after 7 days of a normal diet (100 mg protein/day) and again after 2 and 4 weeks of a restricted diet (19 gm protein/day). The renal clearance of oxipurinol was reduced from 19.6 +/- 1.5 ml/min during the normal diet to 10.9 +/- 0.8 and 12.0 +/- 0.9 ml/min (both P less than 0.001) during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
1
2
1
Order By: Relevance
“…In 3 of our studies we measured acetoacetate and fJ-hydroxybutyrate concentrations to evaluate ketone bodies as competitive inhibitors of uric acid and oxipurinol renal elimination (Kitt et al 1988(Kitt et al , 1989Park et al 1987). Our data do not support the hypothesis that elevation of plasma ketone bodies during the low-protein diet explained the reduction in renal clearance of those compounds.…”
Section: Possible Mechanisms For Changes In Renal Functioncontrasting
confidence: 53%
See 3 more Smart Citations
“…In 3 of our studies we measured acetoacetate and fJ-hydroxybutyrate concentrations to evaluate ketone bodies as competitive inhibitors of uric acid and oxipurinol renal elimination (Kitt et al 1988(Kitt et al , 1989Park et al 1987). Our data do not support the hypothesis that elevation of plasma ketone bodies during the low-protein diet explained the reduction in renal clearance of those compounds.…”
Section: Possible Mechanisms For Changes In Renal Functioncontrasting
confidence: 53%
“…Our data do not support the hypothesis that elevation of plasma ketone bodies during the low-protein diet explained the reduction in renal clearance of those compounds. Although plasma ketone bodies increased by almost a factor of 3 during the protein-and calorierestricted diet, previous studies suggested that 60-to 80-fold elevations were required to reduce uric acid renal clearance (Goldfinger et al 1985;Park et al 1987). However, even stronger evidence was produced in our study of isocaloric diets that showed that the changes in renal clearance of oxipurinol and uric acid occur in the absence of any change in plasma ketone bodies (Kitt et al 1988).…”
Section: Possible Mechanisms For Changes In Renal Functionsupporting
confidence: 36%
See 2 more Smart Citations